Exploring Consequences of Guilt in Working Mothers: A Scoping Review - Hairina, Yulia; Hartini, Nurul (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Guilt is defined as part of the negative emotions that arises related to the conflict between work and family, especially in working mothers. Therefore, this study aimed to examine the consequences of guilt in working mothers due to role conflict or efforts to balance the roles. The Arksey and O’Malley (2005) framework was used as the study methodology which included searching four databases namely Scopus, WoS, Emerald, and Science Direct. A review of 10 out of 894 published articles identified three categories of consequences related to guilt such as (1) consequences for child care, (2) consequences for work, and (3) consequences for theindividual. The results from this review would provide a more comprehensive understanding of the consequences of guilt experienced by working mothers. These insights were valuable for practitioners, experts, and policymakers. Additionally, it could serve as a foundation for further and in-depth publications such as intervention or qualitative studies exploring the individual experiences of working mothers in greater detail.